Analisis Determinan Yang Mempengaruhi Pengungkapan Corporate Social Responsibility - Muhammad Firza Alpi; Dini Aprilia (Jurnal Akuntansi dan Pajak, 2021)
This study aims to determine the effect of company size, size of the board of commissioners, and profitability on corporate social responsibility listed on the Indonesia Stock Exchange for the 2014-2018 period. This research approach uses an associative research approach. The data collection method is done by documenting data sourced from the annual reports of the Indonesia Stock Exchange. Based on the sample collection, which is done by using a check list according to the criteria, the number of research samples is 6 companies from 15 populations. research samples during the period 2014-2018 and data analysis techniques in this research are descriptive statistics, classic assumption tests which include normality test, multicollinearity test, and heteroscedasticity test, multiple linear regression analysis, hypothesis testing which includes t test, f test and coefficient of determination. The results show that company size has a positive but insignificant effect on disclosure of corporate social responsibility, size of the board of commissioners has a positive but not significant effect on disclosure of corporate social responsibility, and profitability has a positive but not significant effect on disclosure of corporate social responsibility in automotive companies listed in Indonesia Stock Exchange for the period 2014-2018).